2013
DOI: 10.1364/ol.38.000474
|View full text |Cite
|
Sign up to set email alerts
|

Distorted Dammann grating

Abstract: We introduce the Dammann phase-encoding method into original distorted gratings and propose a modified distorted grating, called a distorted Dammann grating (DDG), to realize multiplane imaging of several tens of layers within the object field onto a single image plane. This property implies that the DDG makes it possible to achieve simultaneously high axial resolving power and large axial imaging range without scanning. This DDG should be of high interest for its potential applications in real-time three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The diffraction was asymmetric with one side diffraction intensity being higher in the first order than the other one in all the structures ( Figure 3a-b). The positive orders were less intense because the diffraction was affected by the direction of the curved structures, producing highly intense focal points ( ) on one side and ƒ defocused low intensity spots on the other side 19 .…”
Section: Optical Characterization Of the Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffraction was asymmetric with one side diffraction intensity being higher in the first order than the other one in all the structures ( Figure 3a-b). The positive orders were less intense because the diffraction was affected by the direction of the curved structures, producing highly intense focal points ( ) on one side and ƒ defocused low intensity spots on the other side 19 .…”
Section: Optical Characterization Of the Structuresmentioning
confidence: 99%
“…Geometrical theory for diffraction (GTD) was used to simulate 635 nm illumination beam from 5° to 35° tilt angle patterned structure ( Figure 3c). In addition, the light intensity reduced as the diffraction angle increased because the structure spacing reduced 19,38,39 . The intensity of the CP structures was higher than the SP structures, especially in the larger spacings.…”
Section: Optical Characterization Of the Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work, Hajj et al applied this technique to stochastic optical reconstruction microscopy (STORM) and demonstrated snapshot 3D superresolution imaging of a living cell [145]. In another follow-up work, Yu et al demonstrated that the number of depth layers for simultaneous imaging can be dramatically increased to ~50 by introducing Dammann phase-encoding into the original distorted grating [146]. …”
Section: Snapshot Multidimensional Imaging Implementations and Appmentioning
confidence: 99%
“…The idea of these kinds of grating was first proposed by Dammann and Gortler in 1971 to obtain multiple images from one input object for optical lithography [21]. Later on, the DGs have been proposed for using in lots of interesting application, such as laser beam summation [22], optical interconnections [23], three-dimensional (3D) optical imaging [24], 3D lattice structures generation [25], and optical communication [26]. Moreover, by modifying the grating structure, the optical function of the DG is also extended to be more versatile such as the generation of array of diffractive orders with different vortex phase distribution [26,27].…”
Section: Introductionmentioning
confidence: 99%